Health Worker Retention in Faith-Based Hospitals: A Mediated–Moderated Framework of Employee Engagement and Islamic Work Ethic - Maqfirah, Siti; Abd. Majid, M. Shabri; Putra, Teuku Roli Ilhamsyah; Agustina, Maulidar (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study addresses the gap by developing an integrated framework that incorporates employee engagement and Islamic work ethic into health worker retention strategies. Research Objectives: This study investigates the effects of talent management and employer branding on health worker retention through employee engagement and Islamic work ethic in private faith-based hospitals. Research Methods: Primary data were collected from 210 health workers employed at private hospitals across Aceh Province using a multi-stage random sampling design. This study uses PLS-SEM to estimate direct, indirect, and moderating effects. Empirical Results: The findings indicate that talent management and employer branding significantly strengthen employee retention both directly and indirectly through employee engagement, confirming partial mediation. Islamic work ethic further reinforces these relationships, highlighting that retention is shaped by the interaction between psychological engagement and religiously grounded work values. Implications: The study highlights the importance of integrating human resource practices, employee engagement, and ethical values to sustain workforce retention in faith-based healthcare institutions. JEL Classification: M12, J28, Z12